2015
DOI: 10.1002/jmv.24080
|View full text |Cite
|
Sign up to set email alerts
|

MBL2polymorphisms in women with atypical squamous cells of undetermined significance

Abstract: Infection with high risk Human papillomavirus (HPV) is the main known cause of cervical cancer. HPV induces different grades of lesions: among them, Atypical squamous cells of undetermined significance are abnormal lesions that could evolve in pre-cancer lesions or spontaneously regress. The mannose binding lectin (MBL) is an innate immunity serum protein also found in cervico-vaginal mucosa, whose expression is known to be affected by polymorphisms in exon 1 and promoter of the MBL2 gene. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Conversely, it has been reported that specific functional polymorphisms in the MBL2 gene could increase women's susceptibility to infection by high-risk HPV genotypes due to low MBL serum levels [14][15][16]. In addition, Zupin et al [24] suggested a possible association between MBL2 polymorphisms responsible for low MBL production and susceptibility to the development of atypical squamous cells of undetermined significance.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been reported that specific functional polymorphisms in the MBL2 gene could increase women's susceptibility to infection by high-risk HPV genotypes due to low MBL serum levels [14][15][16]. In addition, Zupin et al [24] suggested a possible association between MBL2 polymorphisms responsible for low MBL production and susceptibility to the development of atypical squamous cells of undetermined significance.…”
Section: Discussionmentioning
confidence: 99%